2003
DOI: 10.2337/diacare.26.11.2994
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and the Risk of Gestational and Pregestational Diabetes in Two Consecutive Pregnancies

Abstract: OBJECTIVE -Cigarette smoking during pregnancy may increase the risk of gestational diabetes mellitus (GDM) or pregestational diabetes mellitus (PDM). Smoking has been associated positively with hyperinsulinemia and insulin resistance in experimental studies, although the association with diabetes remains unclear. To further explore this issue, we examined the association with smoking in the largest prospective cohort study of GDM and PDM to date. RESEARCH DESIGN AND METHODS-The study population comprised 212,1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 31 publications
2
28
0
3
Order By: Relevance
“…Smoking as a risk factor for gestational diabetes has been less studied, with mixed findings. A study (62), different from ours, found increased risk with smoking, while others found no statistically significant association (63)(64)(65). Fatness has been associated with a greater frequency of gestational diabetes (66.67) and is inversely associated with smoking habits (68.69).…”
Section: Discussionmentioning
confidence: 87%
“…Smoking as a risk factor for gestational diabetes has been less studied, with mixed findings. A study (62), different from ours, found increased risk with smoking, while others found no statistically significant association (63)(64)(65). Fatness has been associated with a greater frequency of gestational diabetes (66.67) and is inversely associated with smoking habits (68.69).…”
Section: Discussionmentioning
confidence: 87%
“…The wide confidence interval in the study by Yang et al suggests a lack of precision in the estimate, since only two of the diabetic pregnant women were smokers 29,42 . Other studies have not found this association 21,35,44 . Berkowitz et al 35 did not include cigarette smoking in the multivariate analysis and, therefore, had not adjusted its effect for the effects of other variables; and Innes et al 21 and Terry et al 44 carried out studies with young pregnant women, with average ages of 21 and 24 respectively, probably with less time of exposure to smoking.…”
Section: Cigarette Smokingmentioning
confidence: 81%
“…Other studies have not found this association 21,35,44 . Berkowitz et al 35 did not include cigarette smoking in the multivariate analysis and, therefore, had not adjusted its effect for the effects of other variables; and Innes et al 21 and Terry et al 44 carried out studies with young pregnant women, with average ages of 21 and 24 respectively, probably with less time of exposure to smoking. One methodological problem of the studies was that some studies 21,29,35 classified women as smokers (at least one cigarette per day) or non-smokers, without considering the exposure period.…”
Section: Cigarette Smokingmentioning
confidence: 81%
“…These results disagree with Bertolini et al 18 , which demonstrated that smoke-exposed rats during pregnancy presented no alterations on the litter weight and reduced maternal weight gain. Studies with women pregnant smokers showed contradictory results about maternal weight gain 19,20,21 . The association of diabetes and cigarette smoke impaired maternal weight gain and litter gain, fetal weight and number of fetus (data not shown).…”
Section: Discussionmentioning
confidence: 99%